Ответы и объяснения

2013-02-01T13:00:32+04:00

(1-3y+4y)(1-3y-3)=0

(1+y)(-2-3y)=0

(1+y)(2+3y)=0

2+5y+3y^2=0

D=25-24=1

y1=1

y2=-2/3

 

x1=-2

x2=3

Лучший Ответ!
  • Katyuha85
  • почетный грамотей
2013-02-01T13:09:15+04:00

(х+4у)(х-3)=0

х+3у=1

 

из второго уравнения выразим х:

х = 1-3у

и поставим в первое:

(1-3у+4у)(1-3у-3)=0

(1+у)(-3у-2)=0

расскрываем скобки:

-3у - 3у²-2-2у=0

-3у²-5у-2=0

3у²+5у+2=0

D = 25 -4*3*2 = 25-24=1 >0 ⇒ 2 корня

у₁ = (-5+1)/6 =-4/6 = -2/3

у₂ = (-5-1)/6 =-6/6 = -1

Если у = -2/3, то х = 1+ 3*2/3 = 1+2 =3

Если у = -1, то х = 1+3 = 4

 

Ответ:(3; -2/3); (4; -1).